Mineral nutrient signaling controls photosynthesis: focus on iron deficiency-induced chlorosis. (May 2022) - Therby-Vale, Rebecca; Lacombe, Benoit; Rhee, Seung Y.; Nussaume, Laurent; Rouached, Hatem
Abstract : Photosynthetic organisms convert light energy into chemical energy stored in carbohydrates. To perform this process, an adequate supply of essential mineral elements, such as iron, is required in the chloroplast. Because iron plays a crucial role during electron transport and chlorophyll formation, iron deficiency alters photosynthesis and promotes chlorosis, or the yellowing of leaves. Intriguingly, iron deficiency-induced chlorosis can be reverted by the depletion of other micronutrients [i.e., manganese (Mn)] or macronutrients [i.e., sulfur (S) or phosphorus (P)], raising the question of how plants integrate nutrient status to control photosynthesis. Here, we review how improving our understanding of the complex relationship between nutrient homeostasis and photosynthesis has great potential for crop improvement. Highlights: Photosynthesis is modulated by mineral nutritional crosstalk. Phenotypes of photosynthesis in response to combinatorial nutrient stress cannot be predicted from the responses to individual stresses. Iron deficiency-induced chlorosis can be prevented by combining nutrient stresses. Iron deficiency-induced chlorosis can be prevented by modulating antioxidant homeostasis.